Analysis and Potential of Artificial Intelligence in Making Interactive Teaching Materials for Muhammadiyah Elementary School Teachers in Yogyakarta - Maulinda, Shindy; Putra, Lovandri Dwanda (Universitas Sebelas Maret, 2024)
The background to this research is that in the digital era, education requires innovative approaches to improve the quality of teaching. AI can be used to customize teaching materials according to individual student needs, increase interactivity, and provide more accurate feedback. Teachers can utilize AI to save time when preparing teaching materials, which in turn increases efficiency in the teaching process. This research aims to explore the potential of using AI to provide relevant, interactive teaching materials for teachers. This type of research is qualitative descriptive research. The subjects in this research were school principals and class teachers. This research was conducted in three schools, namely: 1) SD Muhammadiyah Karangbendo, 2) SD Muhammadiyah Karangkajen II, and 3) SD Muhammadiyah Condongcatur. The object of this research was to determine the potential of AI in creating interactive teaching materials. Data collection techniques included interviews, observation, and documentation. Data were then analyzed using the Miles and Huberman model, namely the stages of data collection, data reduction, data presentation, and conclusion drawing. Meanwhile, the data validity was tested using source triangulation. The results of research conducted in three schools, i.e., SD Muhammadiyah Karangbendo, SD Muhammadiyah Condongcatur, and SD Muhammadiyah Karangkajen II, concluded that AI technology provides significant benefits and potential for teachers in various aspects. Overall, the use of AI technology in education, especially in creating interactive teaching materials, provides benefits that can increase the efficiency and quality of learning in the education 4.0 era. AI technology also helps teachers improve the quality of learning and teaching, making learning more interesting, interactive, and effective.